2020
DOI: 10.1002/cam4.2851
|View full text |Cite
|
Sign up to set email alerts
|

The impact of squamous cell carcinoma histology on outcomes in nonmetastatic pancreatic cancer

Abstract: Background The prognosis for nonmetastatic, primary pancreatic squamous cell carcinoma (SCC) is thought to be poor compared with adenocarcinoma (AC); however, this is based on limited data. Additionally, the optimal definitive treatment strategy for nonmetastatic pancreatic SCC is unknown. Methods We analyzed patients with nonmetastatic pancreatic cancer using the National Cancer Database for patients diagnosed from 2006 to 2014. Patients were analyzed according to histology—only AC, adenosquamous carcinoma (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…There is no standard management strategy for this disease owing to the limited current clinical data on SCCP treatment ( 3 ). Therefore, the appropriate management strategy for this disease should be standardized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no standard management strategy for this disease owing to the limited current clinical data on SCCP treatment ( 3 ). Therefore, the appropriate management strategy for this disease should be standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with locally advanced tumors who received neoadjuvant chemo-radiotherapy had better OS than those who did not ( 4 ). However, some studies suggest that neoadjuvant therapy may be unnecessary if the primary SCCP is resectable ( 3 ). Tella et al demonstrated that postoperative radiotherapy and/or chemotherapy did not improve the median OS in patients with stage I-II disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the other types of PC, surgical resection is the only curative approach for ASPC and SCC , that can significantly improve survival[ 107 , 110 , 119 , 120 ]. Patients affected by ASPC or SCC undergoing surgery and post-operative treatment with chemotherapy, radiotherapy or both appear to have a benefit[ 108 , 121 - 123 ], even though there is no consensus regarding the best regimen to use, that are commonly fluoropyrimidine-based, gemcitabine based or platinum-based. Data from Johns Hopkins Hospital show, in particular, benefit for ASPC patients treated with platinum-based chemotherapy, with a mOS of 19.1 mo[ 121 ].…”
Section: Adenosquamous Carcinoma and Squamous Cell Pancreatic Carcinomentioning
confidence: 99%
“…The incidence of PASC only accounts for about 1–4% of pancreatic cancer ( 2 ). The pathological manifestation is that a number of squamous cells are mixed with the adenocarcinoma cell population ( 3 ). The diagnostic criteria is that squamous cells account for at least 30% of all tumor cells in the carcinoma ( 1 ).…”
Section: Introductionmentioning
confidence: 99%